2020
DOI: 10.1016/j.wneu.2020.07.183
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Outcomes of Less Invasive Temporary Internal Distraction Followed by Staged Pedicle Screw Instrumentation in Adolescents with Severe Idiopathic Scoliosis at 2-Year Minimum Follow-Up

Abstract: Study Design. A single-center, retrospective study with a minimum 2-year follow up.Objectives. To describe and report the outcomes of minimal invasive temporary internal distraction (MI-TID) in the surgical treatment of adolescents with severe idiopathic scoliosis (SS).Summary of Background Data. Temporary internal distraction rod is one of the surgical options in severe scoliosis to avoid preoperative halo traction or vertebral column resection. This technique can be applied in a single session or staged and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…As an alternative to external traction techniques that use Halo traction, we can use internal traction-the TID method-in various configurations [16,19,20,24,[40][41][42]. We found that one study compared the outcomes of a Halo gravity traction course with temporary internal distraction [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As an alternative to external traction techniques that use Halo traction, we can use internal traction-the TID method-in various configurations [16,19,20,24,[40][41][42]. We found that one study compared the outcomes of a Halo gravity traction course with temporary internal distraction [26].…”
Section: Discussionmentioning
confidence: 99%
“…The surgical intervention for patients in the G2 cohort was bifurcated into two stages. A refined version of the internal distraction techniques elucidated by Buchowski et al [16] and Skaggs et al [17], extensively expounded upon by Grabala and Helenius [24], was implemented during the surgical intervention. In essence, during the initial procedure, akin to minimally invasive surgical strategies for the standard deployment of growing rods across the proximal thoracic and lower lumbar spinal levels, segmental screws were situated, accompanied by posterior column osteotomies, typically within the exposed upper and lower spinal regions.…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 10 ] Some authors have also used preoperative traction or internal distraction as a part of a staged correction, in order to achieve better correction and shorter fusion. [ 11 12 13 14 15 16 17 ] However, preoperative traction implies an increased risk of perioperative complications such as pin loosening, pin tract infection, and cranial nerve palsies. [ 11 12 13 14 15 16 17 ] Combined anterior and posterior or all-posterior vertebral column resection has also been used to treat severe and rigid scoliosis, but this demanding procedure is affected by a considerably high rate of perioperative complications.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 12 13 14 15 16 17 ] However, preoperative traction implies an increased risk of perioperative complications such as pin loosening, pin tract infection, and cranial nerve palsies. [ 11 12 13 14 15 16 17 ] Combined anterior and posterior or all-posterior vertebral column resection has also been used to treat severe and rigid scoliosis, but this demanding procedure is affected by a considerably high rate of perioperative complications. [ 18 19 20 ] Then, the introduction of all pedicle screws constructs allowed the all-posterior procedures to gradually gain popularity due to the high reliability of three-columnar fixation systems.…”
Section: Introductionmentioning
confidence: 99%